PENEGAKAN HUKUM PIDANA TERHADAP PENYALAHGUNAAN IJIN KEIMIGRASIAN MENURUT UNDANG-UNDANG RI NO. 9 TAHUN 1992 TENTANG KEIMIGRASIAN - Kusuma, Yusuf Perdana (2011)
In general, this research aims: (1) To find out what the factors causing the occurrence of criminal misuse of immigration permits. (2) To find out how the crime prevention efforts on immigration permit abuse. (3) To find and examine further how the role of law enforcement agencies in tackling the criminal misuse of immigration permits. In this study, researchers take a place at the Immigration Office in Yogyakarta, for violation of immigration permit. Data collection techniques using library research and field research. The data analysis technique used is the qualitative normative analysis techniques. Results of research: (1) Factors causing the abuse of immigration permits are: a) The scope of a visa on arrival that is too broad which include tourism activities, social, cultural and business that was originally intended to regulate strictly the visa-free facility, b) There is a grace development time in granting visa-free facilities for tourism, c) the role of officer / officer / immigration officer is huge. (2) Efforts to cope with the occurrence of an act which violates the provisions of the immigration permit divided in two ways: a) reduction in preventive countermeasures are undertaken in an attempt to prevent or maintain the possibility that the occurrence of immigration offenses in this case the crime of misuse of immigration permits , b) the repressive response of this can be done by way of punishment, deportation or black list. (3) Sanctions imposed by law enforcement officials in cases of criminal abuse of the immigration permit is more frequent in non pro justitia, which may include action on immigration, one of which deportation.